Using an electronic patient reported outcome measure (ePAQ-MPH) to assess potential harm for long-waiting patients in gynaecology - Thomas Gray; Sandra Johnson; Edward Prosser-Snelling; Paul Simpson (BMC Women's Health)
Abstract Background During the COVID-19 pandemic, outpatient waits for gynaecology appointments increased by 60% in the UK National Health Service (NHS). The aim of this study was to use the electronic Personal Assessment Questionnaire-Menstrual, Pain and Hormonal (ePAQ-MPH) electronic patient reported outcome measure (ePROM) to assess symptoms, impact and potential harm for patients waiting > 60 weeks for general gynaecology appointments at a teaching hospital. Methods 1070 patients waiting > 60 weeks for a new appointment (range 60–72 weeks) were invited to complete ePAQ-MPH online to measure gynaecological symptoms and health-related quality-of-life (HRQoL). Patients could also call to cancel appointments no longer needed. Non-responders were telephoned weekly for three further weeks and asked to complete ePAQ-MPH. Patients scoring > 80/100 for ePAQ-MPH domains relating to HRQoL had their appointment escalated to be seen within six-eight weeks. Thematic content analysis was undertaken of free-text concerns recorded using ePAQ-MPH. Results 526 patients completed ePAQ-MPH (49.2%), 169 of these scored greater than 80/100 for one or more HRQoL domains and were seen within 6–8 weeks. 103 patients (9.6%) requested to cancel their appointment. Reasons included problem resolving spontaneously (33%), problem treated by general practitioner (10%) and being seen by a private provider (28%). Commonly recorded free-text concerns related to wanting a diagnosis (n = 142), management of condition (n = 98) and pain management (n = 77). Conclusions ePAQ-MPH may be used effectively to prioritise patients waiting for an outpatient appointment in gynaecology. Wider use of ePROMs to support waiting list validation within the NHS and elsewhere should be considered.